Cryoglobulinaemia and rheumatic manifestations in patients with hepatitis C virus infection. Issue 12 (1st December 1998) - Lee, Young Ho; Ji, Jong Dae; Yeon, Jong Eun; Byun, Kwan Soo; Lee, Chang Hong; Song, Gwan Gyu
Abstract : OBJECTIVES: To investigate the association of cryoglobulinaemia and rheumatic manifestations in Korean patients with hepatitis C virus (HCV) infection. METHODS: Forty nine Korean patients with HCV infection were recruited. The prevalence, concentration, and type of cryoglobulin (by immunofixation), rheumatoid factor (RF), antinuclear antibody (ANA), and various rheumatological symptoms were investigated and HCV genotype was determined by polymerase chain reaction with genotype specific primer. RESULTS: The prevalence of cryoglobulin was 59% in Korean HCV patients and the concentration of cryoglobulin was 9.8 (7.9) g/l (mean (SD)). The type of cryoglobulinaemia was identified in 23 (80%) of 29 HCV patients with cryoglobulinaemia and they were all type III. There were no differences in age, sex, history of operation and transfusion, proportion of liver cirrhosis between the patients with cryoglobulinaemia and those without cryoglobulinaemia. The frequencies of RF and ANA were 14% and 3.4% respectively in HCV patients with cryoglobulinaemia. There was no difference in HCV genotype between the patients with cryoglobulinaemia and those without cryoglobulinaemia. Clinical features of HCV patients were as follows: arthralgia/arthritis (35%), cutaneous manifestation (37%), Raynaud's phenomenon (8%), paresthesia (44%), dry eyes (22%), dry mouth (10%), oral ulcer (33%), and abdominal pain (14%). However, these rheumatological symptoms did not differ between the two groups. CONCLUSION: Although the rheumatological symptoms were not different between HCV patients with and without cryoglobulinaemia, HCV patients showed various rheumalogical manifestations. These result suggests that HCV infection could be included as one of the causes in patients with unexplained rheumatological symptoms.